A Qualitative Analysis of Innovation Adoption in the Olive Oil Extraction Process - Zoccali, Domenico; Gadanakis, Yiorgos (My University, 2019)
Pressures on the Italian olive oil sector have increased over the past few years due to seasons of bad weather, small innovation capacity and limited long-term investment plans. Thus, it is of interest to explore signs of positive attitude towards innovation investment in the agricultural sector. The focus has been on technologies employed in the extraction process, since yield and quality of olive oil are mostly affected by this stage. To define the determinants of innovation adoption, 13 managers were interviewed. Questions covered organisation factors, personal factors, social factors, the impact of the olive oil value chain and the cost of the extraction machinery. The results of the thematic analysis showed that determinants of innovation adoption were: perceived usefulness, personal innovativeness, prior experience, influence of peers, training and managerial support, and the relative importance of quality, while major challenges are the lack of financial funds, demand pressure from customers, and lack of early warning systems to tackle bad weather conditions.
Keywords: Olive oil; determinants; innovation adoption; Italy; Lazio Region; Olive oil extraction